A fully heterogeneous catalyst Br-LDH for the cycloaddition reactions of CO2 with epoxides. Issue 48 (29th May 2019) - Wang, Yanyan; Li, Shaopeng; Yang, Youdi; Shen, Xiaojun; Liu, Huizhen; Han, Buxing
Abstract : An easily prepared fully heterogeneous catalyst Br-LDH for the cycloaddition reactions of epoxides with CO2 . Abstract : Herein, we developed a fully heterogeneous catalyst (Br-LDH), where the bromide and the hydroxyl are combined in layered double hydroxides (LDH) and cooperate very well in promoting the cycloaddition of CO2 with epoxides. The selectivity and yield of propylene carbonate could reach 95.5% and 92.0%, respectively.